2012
DOI: 10.1021/om2009793
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Nickel and Palladium Fluoride Complexes with PCP Pincer Ligands. NMR-Based Assessment of Electron-Donating Properties of Fluoride and Other Monoanionic Ligands

Abstract: A series of complexes of the type [( iPr PCP)M-L ] ( M = N i , P d ) , c o n t a i n i n g t h e 2 , 6 -b i s -(diisopropylphosphinomethyl)phenyl ( iPr PCP) pincer ligand and simple monoanionic ligands L (F, Cl, Br, H, Me, Ph, NO 3 , and OTf), have been synthesized and characterized. The fluoride derivatives [( iPr PCP)M-F] were prepared from the halides [( iPr PCP)M-X] (M = Ni, X = Br; M = Pd, X = I) by exchange reactions with AgF or, alternatively, by protonolysis of the methyl complexes [( iPr PCP)M-Me] wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
47
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 74 publications
10
47
0
Order By: Relevance
“…Such p-d non-bonding repulsions are expected to be more intense in the second-row than in firstrow transition elements. [12,21] Notwithstanding these differences, the absolute CO 2 insertion barriers are both low, 11.5 kcal/mol for Ni and 7.9 kcal/mol for Pd, and the global free-energy change is favourable for both reactions (-5.7 and -8.7 kcal/mol, respectively). Therefore both hydroxides are predicted to react easily and quantitatively with CO 2 , as observed experimentally.…”
Section: /Kap1mentioning
confidence: 99%
See 1 more Smart Citation
“…Such p-d non-bonding repulsions are expected to be more intense in the second-row than in firstrow transition elements. [12,21] Notwithstanding these differences, the absolute CO 2 insertion barriers are both low, 11.5 kcal/mol for Ni and 7.9 kcal/mol for Pd, and the global free-energy change is favourable for both reactions (-5.7 and -8.7 kcal/mol, respectively). Therefore both hydroxides are predicted to react easily and quantitatively with CO 2 , as observed experimentally.…”
Section: /Kap1mentioning
confidence: 99%
“…We have observed previously that the position of this signal has a direct relationship with the σ-donating capacity of the ligand bound to the metal in the trans position. [12] For both the Ni and Pd carbonates, the corresponding resonance is shifted downfield by around 3 ppm relative to that of the corresponding bicarbonate complex. This difference shows that the CO 3 2-ligand is a significantly stronger σ donor than HCO 3 -, in line with the decreased basicity of the latter.…”
Section: Introductionmentioning
confidence: 98%
“…In a recent study of nickel and palladium pincer complexes M( iPr PCP)X with a wide variety of X ligands, it was shown that the chemical shift 13 C(ipso) provides a measure of -bond strength while the difference in chemical shifts  13 C(para)   13 C(meta) probes -bonding. On these measures, fluoride was a very weak σ-bonder but exhibited appreciable -bonding 77. Nickel analogues with other pincer ligands behaved similarly.41e The results reported in the present paper provide a much more quantitative indicator of ionic character in the M-F bond of the d8 complexes than previous approaches, though this does not exclude 4-electron d-22 p repulsions.…”
mentioning
confidence: 54%
“…15,19,24 5c was synthesized through the same method as complex 2c. Complexes 4a, 5b, 6b, 7b, 8b were synthesized according to literature procedures and precedent and were used as precatalysts (Scheme 4).…”
mentioning
confidence: 99%